Evaluation of the economic welfare gains from reducing trade administration costs in Mercosur - Mehmet Nazif; Glenn P. Jenkins (Queen's University, Department of Economics, 2024)
This paper evaluates the potential welfare gains in the Mercosur region of South America as a benefit of improvement to the trade administrations. Improvements to border procedures and processes leading to border procedures can save billions of dollars for the region, create markets for exporters and enhance trade diversification for both imports and exports. Using a microeconomic model, we establish the benefit of improvement to trade administration processes by comparing the cost structures of Mercosur member states to two reference countries, Chile and Canada. We estimate that with recent trade figures, the region would benefit by in excess of USD 15 billion annually from reducing both the import and export sides of the trade administration costs to the level now enjoyed by these two reference countries.
Keywords: F14; F13; D60; 330; trade facilitation; international trade; trade administration costs; trade transaction costs; Latin America; Mercosur